Tackling obesity in areas of high social deprivation : clinical effectiveness and cost-effectiveness of a task-based weight management group programme : a randomised controlled trial and economic evaluation /: clinical effectiveness and cost-effectiveness of a task-based weight management group programme : a randomised controlled trial and economic evaluation. (October 2016) - McRobbie, Hayden
No abstract available